Awake Major Abdominal Surgeries in the COVID-19 Era. (22nd February 2021) - Romanzi, Andrea; Boleso, Nicola; Di Palma, Giuseppe; La Regina, Davide; Mongelli, Francesco; Milanesi, Maria; Putortì, Antonella; Rossi, Fabrizio; Scolaro, Roberta; Zanardo, Michel; Vannelli, Alberto
Abstract : Background . During the outbreak of coronavirus disease 2019 (COVID-19), allocating intensive care beds to patients needing acute care surgery became a very difficult task. Moreover, since general anesthesia is an aerosol-generating procedure, its use became controversial. This strongly restricted therapeutic strategies. Here, we report a series of undeferrable surgical cases treated with awake surgery under neuraxial anesthesia. Contextual benefits of this approach are deepened. Methods . During the first pandemic surge, thirteen patients (5 men and 8 women) with a mean age of 80 years, needing undelayable surgery due to abdominal emergencies, underwent awake open surgery at our Hospital. Prior to surgery, all patients underwent nasopharyngeal swab tests for COVID-19 diagnosis. In all cases, regional anesthesia (spinal, epidural, or combined spinal-epidural anesthesia) was performed. Intraoperative and postoperative pain intensities have been monitored and regularly assessed. A distinct pathway has been set up to keep patients of uncertain COVID-19 diagnosis separated from all other patients. Postoperative course has been examined. Results . The mean operative time was 87 minutes (minimum 60 minutes; maximum 165 minutes). In one case, conversion to general anesthesia was necessary. Postoperative pain was always well controlled. None of them required postoperative intensive care support. No perioperative major complications (Clavien–Dindo ≥3) occurred. Early readmission after surgery never occurred. All nasopharyngeal swabs resulted negative. Conclusions . In our experience, awake laparotomy under regional anesthesia resulted feasible, safe, painless, and, in specific cases, was the only viable option. This approach allowed prevention of the need of postoperative intensive monitoring during the COVID-19 era. In such a peculiar time, we believe it could become part of an ICU-preserving strategy and could limit viral transmission inside theatres.